From Dharma to Sound - Carola Lorea (AЯGOS)
This piece takes as a starting point a close reading of Karénina Kollmar-Paulenz’s work and connects it to ongoing debates intersecting the fields of religious studies, the anthropology of religion, sensory studies, Global South studies and decolonial theory. It argues that attention to the layered history of local language categories that articulate religious difference constitutes a form of intellectual labour towards epistemic justice.